A Hierarchical Description-based Video Monitoring System for Elderly - Mochamad Irwan Nari; Agung Wahyu Setiawan; Widyawardana Adiprawita (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
The increase in the number of elderly motivates academic researchers to develop technologies that can ensure self- sufficiency in their lives. In this research, prototype of an inexpensive video monitoring system for the elderly using a single RGB camera proposed. In the process is divided into two, namely vision and event recognition module. For event recognition, we use a hierarchical description-based approach with three attributes, namely posture (e.g., stand, sit and lie), location (e.g., walking zone, relaxing zone and toilet zone) and duration (e.g., short and long). Output this system is description activity recognized in the text. The experiment result shows our system can provide the effectiveness of the context description.